UPBRINGING IN MODERN SCHOOL (EDUCATION IN THE 21ST CENTURY, 2023)
Researches in the field of theory and practice of upbringing was again actualized at the end of the XX and beginning of the XXI century. Valuable research and publications have appeared, which are necessary and sufficient basis for organizing a productive educational process at school. However, it is quite problematic to recognize the educated process at school as successful due to certain and obvious shortcomings. One of the reasons for this is the insufficient preparation of teachers for the full organization of the education process. To confirm this provision, we carried out appropriate work with 47 teachers from 3 schools in Vanadzor, RA. The results obtained indicate a low level of preparedness of teachers for the organization of relevant activities. The overwhelming majority of respondents have no idea about the principles and methods of upbringing, the criteria for assessing the educational work and upbringing of students, they weren’t able to adequately characterize the guided goal in the classroom, etc. Without solving the issue of full-fledged training and retraining of teachers in the field of educational work, success cannot be expected.
Keywords: Keywords: Upbringing, the goal of upbringing, teacher, pupil, upbringing model, upbringing criteria